2000
DOI: 10.1126/science.287.5451.300
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Abscisic Acid-Induced Stomatal Closure and Anion Channels by Guard Cell AAPK Kinase

Abstract: significant differences between axon-bearing and ax-presented (abstract 291.5) at the 29th Meeting of the 26. A. 8. Ali and A. M. Thomson,]. ~h~s i o l . (london) 507, on-lacking dendrites.Abscisic acid (ABA) stimulates stomatal closure and thus supports water conservation by plants during drought. Mass spectrometry-generated peptide sequence information was used t o clone a Vicia faba complementary DNA, AAPK, encoding a guard cell-specific ABA-activated serine-threonine protein kinase (AAPK). Expression in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
320
2
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 419 publications
(341 citation statements)
references
References 33 publications
9
320
2
9
Order By: Relevance
“…As a result, ABI1 and ABI2 may negatively regulate the anion channels and/or K + channels. This is consistent with the positive regulation of anion channels by AAPK (Li et al 2000). However, because studies on AAPK and ABIs have been conducted in different plants and in a different genetic context, it is premature to conclude whether AAPK and ABIs serve as counteracting kinase and phosphatases in anion channel regulation by ABA.…”
Section: Aapk and Abismentioning
confidence: 52%
See 1 more Smart Citation
“…As a result, ABI1 and ABI2 may negatively regulate the anion channels and/or K + channels. This is consistent with the positive regulation of anion channels by AAPK (Li et al 2000). However, because studies on AAPK and ABIs have been conducted in different plants and in a different genetic context, it is premature to conclude whether AAPK and ABIs serve as counteracting kinase and phosphatases in anion channel regulation by ABA.…”
Section: Aapk and Abismentioning
confidence: 52%
“…Using a biochemical approach, two studies (Li & Assmann 1996;Mori & Muto 1997) identified an ABA-activated protein kinase (AAPK) from guard cells of Vicia faba. Cloning of this kinase and further genetic manipulation in guard cells indicates that AAPK is involved in the regulation of the slow anion channel by ABA (Li et al 2000). Because AAPK is not regulated by Ca 2+ , AAPK regulation of the anion channel is located in the Ca 2+ -independent branch of ABA signalling pathway.…”
Section: Aapk and Abismentioning
confidence: 99%
“…First came the cloning and characterization of a V. faba Ca 2+ -independent ABA-activated protein kinase (AAPK) [100][101][102], with an ortholog in Arabidopsis named OST1 [103]. Expression of a dominant negative form of AAPK resulted in insensitivity of ABA-induced closure of guard cells and impaired ABA-activation of S-type anion currents.…”
Section: Anion Channels: Roles In Guard Cell Signal Transductionmentioning
confidence: 99%
“…Plants live in soil-plant-atmosphere continuum (SPAC) environment, and they have to coordinate the mechanisms of diverse types to respond to the above changing environment at any time for sustainable survival [4][5][6][7][8][9][21][22][23][24][25][26][27][28][29][47][48][49][50][51][52][53][54][55][56][57][58][59]. Plant production realization is obtained eventually through physiological pathways at least at the level of individual and community [102][103][104][105][106][107][108][109]120,[130][131][132][133][134][135][136][137][138][139][140].…”
Section: Physiological Theories: Understanding Higher Plant Physiologmentioning
confidence: 99%